Reversal of the hofmeister series: specific ion effects on peptides - Paterová, Jana; Rembert, Kelvin B; Heyda, Jan; Kurra, Yadagiri; Okur, Halil I; Liu, Wenshe R; Hilty, Christian; Cremer, Paul S; Jungwirth, Pavel (The journal of physical chemistry. B, 2013)
Ion-specific effects on salting-in and salting-out of proteins, protein denaturation, as well as enzymatic activity are typically rationalized in terms of the Hofmeister series. Here, we demonstrate by means of NMR spectroscopy and molecular dynamics simulations that the traditional explanation of the Hofmeister ordering of ions in terms of their bulk hydration properties is inadequate. Using triglycine as a model system, we show that the Hofmeister series for anions changes from a direct to a reversed series upon uncapping the N-terminus. Weakly hydrated anions, such as iodide and thiocyanate, interact with the peptide bond, while strongly hydrated anions like sulfate are repelled from it. In contrast, reversed order in interactions of anions is observed at the positively charged, uncapped N-terminus, and by analogy, this should also be the case at side chains of positively charged amino acids. These results demonstrate that the specific chemical and physical properties of peptides and proteins play a fundamental role in ion-specific effects. The present study thus provides a molecular rationalization of Hofmeister ordering for the anions. It also provides a route for tuning these interactions by titration or mutation of basic amino acid residues on the protein surface.
Keywords: Oligopeptides; ionty; Molecular Dynamics Simulation; Ions; magnetická rezonanční spektroskopie; peptidy; Magnetic Resonance Spectroscopy; simulace molekulární dynamiky; oligopeptidy; Peptides